Application Of A Guided Inquiry Learning Model In The Context Of A Socio Scientific Issue To Improve The Inquiry And Critical Thinking Skills Of High School Students On Acid Base Material - Gustafo Johansen WIlar; Suwardi (PT Publikasiku Academic Solution, 2025)
This study investigates the impact of guided inquiry learning within the Socio-Scientific Issues (SSI) context on students' inquiry and critical thinking skills in acid-base chemistry learning. With increasing emphasis on 21st-century competencies, inquiry-based and critical thinking skills have become essential in science education. This research aims to compare the effectiveness of the guided inquiry model in the SSI context with the conventional scientific learning model in fostering these skills. A quasi-experimental design involved two student groups exposed to different instructional approaches on the same acid-base material. Data were analyzed using inferential statistics to determine differences in skill development. The findings reveal significant differences in inquiry skills between students taught using the guided inquiry model in the SSI context and those using the scientific learning model. However, the two groups observed no significant differences in critical thinking skills. The effective contribution of both inquiry and critical thinking skills combined was 0.275. Specifically, inquiry skills showed a medium-level effective contribution (0.239), while critical thinking skills demonstrated a low contribution (0.036). These results suggest that while guided inquiry in the SSI context can enhance inquiry ability, its influence on critical thinking may require further pedagogical support. The study highlights the importance of integrating socio-scientific contexts to improve inquiry competence and recommends refining instructional strategies to better support critical thinking development in science classrooms.